Visual Pollution in the Context of Conflicting Design Requirements - Sumartono Sumartono (Journal of Visual Art and Design, 2009)
All designs (graphic, product, and interior designs) are directed to consider certain requirements which are followed by logical thinking to fulfill a design process. Once the requirements of each design have been well-considered and the logical design process has been fulfilled, the design is complete. Ideally, all designs are not supposed to be in conflict with each other because each one is based on a logical design process. In reality, however, the mutual existence of these designs has produced conflicting requirements and thereby conflicting logics. This conflict can be seen in visual pollution. This paper will examine the impact of visual pollution caused by billboards, street signs, posters, houses/buildings, automobiles, shopfront graphic designs, packaging designs, graffiti, etc. in the context of conflicting logics/requirements. Today, opposition grows everywhere against all visually polluting designs and outdoor advertising is the most prominent one. Some people think that it should be banned from the city. Some others, however, think that if advertisements are removed from the city, it will become a bland concrete jungle. Every city in Indonesia needs a clean-city law to control illegal advertisements and signs. It is possible to make legal yet attractive advertisements that will give positive contribution to "visual democracy" in Indonesia.